Production of Oncorhynchus mykiss biosensor based on polyvinyl alcohol/chitosan nanocomposite using phycocyanin during refrigerated storage - Sima Abed; Bahareh Nowruzi; Seyed Amir Ali Anvar (Scientific Reports)
Abstract Smart packaging, also known as intelligent packaging, is responsive to external stimuli, moisture, light, oxygen, heat, pH, and bacterial growth. In this study, polyvinyl alcohol/nanochitosan/phycocyanin nanocomposite (PVA/NCH/PC-NC) for fish fillets of Oncorhynchus mykiss rainbow trout coating was prepared. Five treatments were prepared over a period of 14 days (0, 1, 7 and 14 days) under treatments of T1: fish coated with PVA/NCH-NC without PC; T2, T3, T4 and T5 fish coated with PVA/NCH/PC-NC (0.5, 1, 1.5 and 2% PC respectively). Moreover, the results showed that higher concentrations of PC in PVA/NCH polymer matrix resulted in a net-like morphology on the film's surface. Also, after 21 days of storage, the T4 treatment had the lowest levels of mesophilic, psychrophilic, and Enterobacteriaceae bacteria (8.17 ± 0.02, 7.90 ± 0.04, and 60.67 ± 0.02 log cfu/g, respectively). Additionally, it was seen that PVA/NCH/PC-NC improved the Sensory evaluation of fish fillet samples during 14 days of storage (p < 0.05). Overall, the results showed that the prepared PVA/NCH/PC-NC (2% PC) film function as an intelligent packaging solution in food preservation and freshness monitoring applications of Oncorhynchus mykiss fillet in terms of mechanical, microbial and sensorial evaluation.